Two Phages, phiIPLA-RODI and phiIPLA-C1C, Lyse Mono- and Dual-Species Staphylococcal Biofilms - Gutiérrez, Diana; Vandenheuvel, Dieter; Martínez, Beatriz; Rodríguez, Ana; Lavigne, Rob; García, Pilar (Applied and environmental microbiology, 2015)
Phage therapy is a promising option for fighting against staphylococcal infections. Two lytic phages, vB_SauM_phiIPLA-RODI (phiIPLA-RODI) and vB_SepM_phiIPLA-C1C (phiIPLA-C1C), belonging to the Myoviridae family and exhibiting wide host ranges, were characterized in this study. The complete genome sequences comprised 142,348 bp and 140,961 bp and contained 213 and 203 open reading frames, respectively. The gene organization was typical of Spounavirinae members, with long direct terminal repeats (LTRs), genes grouped into modules not clearly separated from each other, and several group I introns. In addition, four genes encoding tRNAs were identified in phiIPLA-RODI. Comparative DNA sequence analysis showed high similarities with two phages, GH15 and 676Z, belonging to the Twort-like virus genus (nucleotide identities of >84%); for phiIPLA-C1C, a high similarity with phage phiIBB-SEP1 was observed (identity of 80%). Challenge assays of phages phiIPLA-RODI and phiIPLA-C1C against planktonic staphylococcal cells confirmed their lytic ability, as they were able to remove 5 log units in 8 h. Exposure of biofilms to phages phiIPLA-RODI and phiIPLA-C1C reduced the amount of adhered bacteria to about 2 log units in both monospecies and dual-species biofilms, but phiIPLA-RODI turned out to be as effective as the mixture of both phages. Moreover, the frequencies of bacteriophage-insensitive mutants (BIMs) of Staphylococcus aureus and S. epidermidis with resistance to phiIPLA-RODI and phiIPLA-C1C were low, at 4.05 × 10(-7) ± 2.34 × 10(-9) and 1.1 × 10(-7) ± 2.08 × 10(-9), respectively. Overall, a generally reduced fitness in the absence of phages was observed for BIMs, which showed a restored phage-sensitive phenotype in a few generations. These results confirm that lytic bacteriophages can be efficient biofilm-disrupting agents, supporting their potential as antimicrobials against staphylococcal infections.